project3

# project3 - x = x y = y z = z x = 3(2*l y =-1(4*l z = 1(2*l...

This preview shows pages 1–3. Sign up to view the full content.

1) A) syms x y z l e = (x.^2+2*y.^2+3*z.^2-1); dee = [diff(e,x), diff(e,y), diff(e,z)] dee = [ 2*x, 4*y, 6*z] p = 3*x - y + 3*z – 1; dpp = [diff(p,x), diff(p,y), diff(p,z)] dpp = [ 3, -1, 3] dp = l*dpp dp = [ 3*l, -l, 3*l] point = dee - dpp point = [ 2*x - 3, 4*y + 1, 6*z - 3] f = solve('2*x*l = 3', '4*y*l =- 1', '6*z*l=3','x^2+2*y^2+3*z^2-1') f = l: [2x1 sym] x: [2x1 sym] y: [2x1 sym] z: [2x1 sym] [f.x,f.y,f.z,f.l] ans = [ (3*2^(1/2))/5, -2^(1/2)/10, 2^(1/2)/5, (5*2^(1/2))/4] [ -(3*2^(1/2))/5, 2^(1/2)/10, -2^(1/2)/5, -(5*2^(1/2))/4]

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x = x y = y z = z x = 3/(2*l) y =-1/(4*l) z = 1/(2*l) dval = dee[x, y, z] b) syms X Y Z h = [(X-x), (Y-y), (Z-z)] h = [ X - 3/(2*l), Y + 1/(4*l), Z - 1/(2*l)] syms r s x y dot( f=(1-3*x+y)/3; ezsurf(sin(r)*cos(s),(sin(r)*sin(s))/sqrt(2),(cos(r))/sqrt(3)) hold on ezmesh(f,[-1,1,-1,1]) 4) clear all; syms x y z ezsurf(x,(-x.^2-z.^2)/4,z) b) s1 = x.^2+4*y+z.^2 s1 = x^2 + z^2 + 4*y %solving for the tagent of S1 vect = [diff(s1,x), diff(s1,y),diff(s1,z)] vect = [ 2*x, 4, 2*z] vect(0, -1, 2)...
View Full Document

## This note was uploaded on 09/04/2011 for the course MA 280 taught by Professor Profdecir during the Spring '11 term at Montgomery College.

### Page1 / 3

project3 - x = x y = y z = z x = 3(2*l y =-1(4*l z = 1(2*l...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online